2019
DOI: 10.3390/catal9020179
|View full text |Cite
|
Sign up to set email alerts
|

Fluorinated and Platinized Titania as Effective Materials in the Photocatalytic Treatment of Dyestuffs and Stained Wastewater Coming from Handicrafts Factories

Abstract: In this study, commercial and lab-prepared TiO2 were modified by fluorination and platinum photodeposition; and the effect of these modifications over the physicochemical and photocatalytic properties of TiO2 was evaluated. It was found that F and Pt addition leads to the modification of the optical and textural properties of TiO2. The materials prepared were tested in the photocatalytic degradation of different organic dyestuffs such as methylene blue (MB) and methyl orange (MO); the degradation of commercial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…In the case of MC-H series, FT-IR bands do not allow us to clearly distinguish possible bands of nitrogen (e.g., nitro groups at ca. 1330–1530 or 1574 cm −1 ) [ 62 ] or sulfur-containing species (e.g., sulfate groups at 1000–1250 cm −1 ) [ 63 ] resulting from surface functionalization, probably due to their small content and overlap with some other bands. In any case, the above-mentioned XPS results evidenced the presence of sulfur species in both MC and MC-H series, which were more oxygenated in the latter case.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of MC-H series, FT-IR bands do not allow us to clearly distinguish possible bands of nitrogen (e.g., nitro groups at ca. 1330–1530 or 1574 cm −1 ) [ 62 ] or sulfur-containing species (e.g., sulfate groups at 1000–1250 cm −1 ) [ 63 ] resulting from surface functionalization, probably due to their small content and overlap with some other bands. In any case, the above-mentioned XPS results evidenced the presence of sulfur species in both MC and MC-H series, which were more oxygenated in the latter case.…”
Section: Resultsmentioning
confidence: 99%
“…Dye degradation was related to the generation of • OH and • O 2 – radicals, which was dependent on the absorption of UV light by TiO 2 . 31 Through the oxidation reaction with radicals, chromogenic groups (such as −N5N– and −CH5CH−) in dyes were broken, resulting in higher color removal efficiency for CV-RR. It is confirmed that the molecular structure is related to the photocatalytic degradation of dye.…”
Section: Resultsmentioning
confidence: 99%
“…The superior performance was attributed to the nanocomposite’s low resistance and band gap value. Murcia et al [ 115 ] had improved the efficiency of titania catalyst by doping with Pt, along with it, they fluorized them to the commercial P25 and laboratory synthesized titania. The modification offered improvements in physicochemical and photocatalytic properties such as absorption of visible light, lower band gap values, increase surface areas etc.…”
Section: Applications Of Titania As Photocatalystmentioning
confidence: 99%